Magnetocaloric Effect and Universal Curve Behavior in Superparamagnetic Zinc Ferrite Nanoparticles Synthesized Via Microwave Assisted Co-Precipitation Method - Casagrande-Denardin, J (Wiley-VCH Verlag, 2018)
Single domain superparamagnetic zinc ferrite nanoparticles are synthesized through microwave assisted co-precipitation method. Single phase and cubic spinel zinc ferrite nanoparticles shows the narrow particle size distribution with an average particle size of 5.07 nm. They exhibits superparamagnetic nature at 290 K and ferromagnetism at 5 K with a blocking temperature of around 25 K. The magnetic entropy change calculated from the set of isothermal magnetization curves shows the maximum entropy change of −0.652 J kg−1 K−1 at 135 K and large relative cooling power (RCP) of 187 J kg−1 for the field of 40 kOe. The synthesized zinc ferrite nanoparticles exhibits large magnetic anisotropy constant of 12.625 × 106 erg cm−3 with an appreciable magnetic entropy change. The field dependence of maximum magnetic entropy change and RCP values is discussed by using power law equations. Furthermore, an attempt is made to study the phenomenological curve behavior of magnetic entropy change for the zinc ferrite nanoparticles. Interestingly, the magnetic entropy change at the range of magnetic fields collapses into a single universal phenomenological curve when rescaling the temperature axis with two reference temperatures. The obtained results conveys that the zinc ferrite nanoparticles is prospective magnetic refrigerant for miniaturized devices. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim